1988
DOI: 10.1002/jmv.1890260304
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of infection with West Nile virus in Karachi, Pakistan, in 1983 and 1985

Abstract: The prevalence of West Nile (WN) virus infection in Karachi, Pakistan, was unknown until 1982. It had been noticed that there were more than a few patients with encephalitides in Karachi, and it was supposed that Japanese encephalitis (JE) cases would be found among them. Therefore, a seroepidemiological study was conducted to define the prevalence of WN virus infection and the possible occurrence of JE virus infection in the Karachi area. Prevalences of haemagglutination inhibition (HI) and neutralization (NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…A similar situation exists in some areas of India and Pakistan, where both West Nile and JE viruses infect humans. 34,35 The potential exists for JE virus to become established in enzootic cycles on Cape York Peninsula, since there are extensive swamps and wetlands that possess significant populations of wild pigs, ardeid waterbirds, and Cx. annulirostris mosquitoes.…”
Section: Resultsmentioning
confidence: 99%
“…A similar situation exists in some areas of India and Pakistan, where both West Nile and JE viruses infect humans. 34,35 The potential exists for JE virus to become established in enzootic cycles on Cape York Peninsula, since there are extensive swamps and wetlands that possess significant populations of wild pigs, ardeid waterbirds, and Cx. annulirostris mosquitoes.…”
Section: Resultsmentioning
confidence: 99%
“…Occurrence of WNV and JEV has also been reported in countries neighbouring Pakistan (India, China, Iran) [6][7][8]. From 1968 to 1994, a few clinical, serological and epidemiological studies indicated the presence of WNV and JEV in Pakistan [9][10][11][12][13]. Data are totally nonexistent regarding the prevalence of WNV and JEV for the subsequent years.…”
mentioning
confidence: 84%
“…The recent lineage 5 isolates reported from northeastern India were more neuroinvasive and pathogenic in mice than Indian isolates from 1982 and earlier [ 86 ]. Cases of WNND have also been reported from Pakistan along with human seroprevalences ranging from 12 to 54% [ 206 209 ].…”
Section: Wnv In Southern and Eastern Asia Australia And Oceaniamentioning
confidence: 99%